Investigation of VDR gene polymorphisms in twins with autism spectrum disorder. (April 2021) - Coskunpinar, Ender; Kose, Tuba; Demirayak, Pinar Algedik; Hayretdag, Ceyda; Bozlak, Serdar
Highlights: Some variants of the VDR gene cause a predisposition to the disease in dizygotic twins with ASD. TaqI, FokI and TaqI genotypes are a risk factor associated with ASD. In terms of allele frequencies of SNPs, ApaI and TaqI are statistically significant between dizygotic patients and controls. Abstract: Background: Twin studies to clarify the etiology of autism, copy number variations (CNV), and genome-wide association studies (GWAS) have provided strong evidence that genetic factors play an important role in the etiology of Autism spectrum disorder (ASD). The purpose of this study is to determine the relationship between Vitamin D Receptor (VDR) gene polymorphisms and disease development in ASD twins. Method: The study included 32 pairs of dizygotic twins (64 patients) with ASD and 100 healthy subjects as the control group. Genomic DNA was isolated from blood samples. It is performed by PCR designed with region-specific primers. After the PCR procedure, RFLP was performed with appropriate enzymes to determine genotypes. The results were statistically evaluated by Chi Square Test and Haplotype analysis. Results: When the results of our study were examined, the frequency of the variant CC genotype of FokI (rs2228570 T/C), the frequency of the variant TT genotype of ApaI (rs7975253 G/T) and the frequency of the variant TT genotype of TaqI(rs731236 T/C) were significantly higher than the control group (p:0, 019, p:0, 039, p:0, 037). Conclusions: In this study, single nucleotide changes in three different variants of the VDR gene were investigated in dizygotic twins cases with ASD in Turkey. Genotypically, it was found that patients showed statistically significant difference in all three regions compared to controls. In terms of allele frequencies of SNPs, it was observed that ApaI and TaqI allele frequencies were statistically significantly different between dizygotic patients with ASD and healthy controls.